Circulatory Cathelicidin Levels’ Predictive Value for Pediatric Community-Acquired Pneumonia Without COVID-19 - Obed, Ahmed Faisal; Radeef, Asmaa Hamza; Al-Hindy, Hayder Abdul-Amir Makki; Mousa, Mazin J.; Hussein, Omar Taha (International Journal of Membrane Science and Technology, 2023)
: Background: Community-acquired pneumonia (CAP), one of the most common infectious diseases, is the third leading cause of death worldwide. To stop the spread of serious sickness and keep the initial infection under control, the innate immune response is crucial. Cathelicidin, a potent antimicrobial peptide that may kill germs directly and alter the immune system’s response to infection, is an essential component of this response. The main goal of the study is to investigate the association between CaLL37 and the severity of CAP in young patients. Methodology: 120 CAP cases and 165 controls made comprised the 285 participants in this case-control study, whose ages varied from 1 to 18 months. Calculated and compared cathelicidin levels for CAP and control participants as well as the pneumonia-causing agent. People who were thought to have COVID-19 CAP were excluded. Results: The participants’ mean age was 9.7 (range of 1 to 18) months. In 46.2%, 35%, and 18.8% of cases of CAP; bacterial, viral, and mixed causative agents, respectively, were detected. Among the individuals, only 6.8% received mixed feeding, compared to 42.1% who used artificial feeding and 51.1% who exclusively breastfed. The mean total serum contained 8.6 ±6.7 ngof CaLL37. CaLL37 serum levels were comparable between the two study groups (p>0.05). The levels of CaLL37 were comparable (p>0.05) among patients with CAP when compared according to the causative agents, while plasma CaLL37 levels were higher among babies on artificial feeding (p-0.001). The ROC assays revealed that CaLL37 plasma levels were unable to differentiate between bacterial and viral pneumonia or between persons who had pneumonia and healthy subjects. However, the CaLL37 can discriminate between infants who are breastfed and those who are fed by a bottle considerably (p-0.001, AUC=0.748, sensitivity=0.673, specificity=0.637, and 95%CI of o.675 - 0.820). Conclusion: According to the study, CaLL37 is capable of determining the difference between infants who are breastfed and those who are fed artificially. However, it is difficult for cathelicidin to distinguish between various CAP causes as well as between CAP patients and healthy controls.